No People, No News: News Deserts and Areas at Risk in Spain - Negreira-Rey, María-Cruz (2023)
In recent decades Spain has suffered a gradual process of depopulation and exodus from rural areas to large capitals. The España Vaciada political and social movement denounces the country’s territorial inequality, while the government is working on a strategic plan to address the demographic challenge. At the media level, there is concern about citizens’ access to a local and quality journalistic service, key to the strengthening of communities and their democratic functioning. The main objective of this research is to explore the phenomenon of news deserts in Spain, identifying the areas that can be considered news deserts and those that are at risk of becoming so, based on the mapping of digital media in the country. The characteristics of the digital media of the autonomous communities with the highest presence of news deserts are studied to ascertain whether the risk factors of population or richness index are connected to their appearance. The results reveal that 6,304 (77.53%) Spanish municipalities can be considered news deserts, inhabited by 11.6 million people, 24.51% of the country’s total population. In addition, another 523 municipalities are at risk of becoming news deserts. In the regions with the largest number of news deserts, there is a clear concentration of media in the main capitals and a weak ecosystem of local and hyperlocal media. Depopulation is the main risk factor in the loss of media and news coverage in local communities.